THE IMPACT OF SOIL TILLAGE SYSTEM AND PROCEEDING CROPS ON WINTER WHEAT GRAIN YIELD CAPACITY AND QUALITY - Liashenko, V. V.; Karasenko, V. M.; Krakotets, S. I. (Scientific Progress & Innovations, 2021)
The expediency of transition from traditional tillage systems to alternative ensuring soil protection from erosion, preventing humus and moisture loss, and ensuring soil fertility restoration has been substantiated in the article. The purpose of the article is the assessment of different tillage systems and proceeding crops impact on winter wheat grain yield capacity and quality. To achieve it, the following tasks were set and solved: the reserves of productive moisture in the soil were determined; soil density was defined; weed infestation of sown areas was studied; winter wheat grain yield capacity and quality depending on soil tillage systems and proceeding crops were determined. In the fixed experiment, winter wheat was sown after three proceeding crops: weed free fallow, soya, and silage corn. In all the rotation fields, the crop was grown according to three technologies: traditional, minimum, and zero. According to the research results, it has been established that energy saving minimum and zero technologies ensured the obtaining of winter wheat yield gain by 1.4 hundredweight/ha, on the average. At the traditional tillage technology, soil moisture in the upper layer is less than at minimum and zero technologies, while in the deeper layers, no significant difference between technology variants was observed as a result of considerable amount of precipitation before harvesting. The level of winter wheat areas’ weed infestation was the highest at minimum tillage technology after any proceeding crop and the lowest – at the traditional technology, which is a typical phenomenon as a result of mechanical soil tillage limitation. The largest gluten content of winter wheat grain was obtained while using minimum and zero technologies – 24.3 and 24.8 %, respectively, in comparison with the standard technology – 22.9 %. The minimum and zero technologies resulted in a sharp improvement of the sown crop condition after the worst precursor – silage corn. It was especially noticeable on the zero technology variant, at which plant density after this proceeding crop was by 46 % higher than at the traditional one. Thus, under insufficient moisture conditions, there will be more advantages after using minimum and zero technologies.